Uma revisão sobre as investigações construtivistas nas últimas décadas: concepções espontâneas, mudança conceituai e ensino de ciências - Nardi, Roberto [UNESP]; Gatti, Sandra Regina Teodoro [UNESP] (Faculdade de Educação da Universidade Federal de Minas Gerais, 2004)
The constructivist approach in Science Education became a strong influence in the middle of the 70s, with a great emphasis on investigating students' conceptions of a variety of science contents. The attempts to take these results into the science classes originated the research on conceptual change followed by many studies that are still today trying to interfere in classroom teaching. In this chapter we look for presenting some research about spontaneous reasoning in physics carried out in Brazil in that period and to review the main research that followed the pioneer paper on conceptual change published by Posner and his collaborators.

A abordagem construtivista no ensino de Ciências tornou-se influente a partir da década de 70, com a grande ênfase dada as investigações sobre as concepções espontâneas de estudantes sobre diversos conteúdos de ciências. As tentativas de levar os resultados das investigações para a sala de aula originaram as discussões sobre mudança conceituai, seguidas de inúmeros estudos que até hoje têm procurado interferir no ensino de sala de aula. Neste capítulo procuramos mostrar alguns trabalhos sobre concepções espontâneas em física realizados no Brasil naquele período e fazer uma revisão das principais publicações que se seguiram após os trabalhos pioneiros de Posner e colaboradores.
A review of the constructivist research in the last decades: spontaneous reasoning, conceptual change and science education
Keywords: Constructivism; spontaneous reasoning; conceptual change; science teaching.; Construtivismo; concepções espontâneas; mudança conceitual; ensino de ciências.